ﺷﺑﻛﺔ اﻟﺣﻣﺎﯾﺔ اﻻﺟﺗﻣﺎﻋﯾﺔ واﻷﻣن اﻹﻧﺳﺎﻧﻲ ﻓﻲ اﻟﻌراق ﻓﻲ اطﺎر اﻟﺳﯾﺎﺳﺔ اﻻﺟﺗﻣﺎﻋﯾﺔ (Journal of the College of Education for Women, 2019)
This study focuses on Social Protection Net in Iraq considered as one of the phases of social sponsorship taking care of the weak category inside society after the increased poverty such as begging, unemployment and theft… etc. which was a product of striken poverty evoked by the events that Iraqi society have passed through. Accordingly, social sponsorship law number (126) 1980 was unable to solve those problems, there springs a need for building a social protection when the Social Protection Net law started working in Iraq on 1/12/2005 according to a schedule for social assistance depending on number of family members, including new social sections such as the unemployed, blind, orphans underage and other weak sections inside society. This study sheds light on the law of Social Protection Net through its main sections. It aims at satisfying the basic needs of all slices of society, supporting the positive values which affirm social stability like religious values, coordination and role of family in supporting these values. In addition, it helps the weaker sections through productive loans, developing standards of living and education, and preservation from social problems that threaten social stability like poverty, unemployment and social exclusion. It tackles the economic and social effects of applying the law of Social Protection Net such as psychological stability and social security for threatened families because of low income, eliminating or decreasing the phenomena of begging, decreasing elopement of pupils from schools to work, creation of trained body privileged by scientific qualifications, granting small loans to families to enact a new income that might evolve into big projects aiming at serving society, enhancing the citizenship through an important relation between citizen and state by which the citizen feels that the state cares of him in seeking to raise his standard of living, and he/she in turn seeks to serve his/her country as much as possible. The economic effects include a certain of new economic activity contribute in the development of Iraqi economy through granting loans to start small projects, achieving equality in distributing income, decreasing the percentage of unemployment in Iraq by training them, and prepare a qualified body to lead and participate in the process of economic development. Concerning human security it depends on economic security, for limited income families and the down trodden, as one of the fields of human security that is related to human rightsthrough achieving security for every individual in society. The fourth section deals with the role of social politics in diminishing poverty through mechanism of Social Protection and strategy on which it depends to reduce poverty line in Iraq. The study ends with a bunch of findings and recommendations that enable decision makers achieve better results when they apply the law of Social Protection Net.